2015
DOI: 10.1007/s11920-015-0598-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Disaster Reactions: the Influence of Exposure and Personal Characteristics

Abstract: This paper reviews children's reactions to disasters and the personal and situational factors that influence their reactions. Posttraumatic stress disorder (PTSD) and posttraumatic stress reactions are the most commonly studied outcomes, though other conditions also occur including anxiety, depression, behavior problems, and substance use. More recently, traumatic grief and posttraumatic growth have been explored. New research has delineated trajectories of children's posttraumatic stress reactions and offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 50 publications
(45 reference statements)
0
40
0
1
Order By: Relevance
“…Empirical research on children with disabilities exposed to disaster or terrorism is extremely limited and much work remains to be done in this area. First, while most children are psychologically resilient and do not develop psychopathology following disaster or terrorism [36], we know little about the resiliency of children with disabilities under the same circumstances. Second, the mental health of individuals with disabilities post-disaster/terrorism has been substantially overlooked by both researchers and clinicians [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research on children with disabilities exposed to disaster or terrorism is extremely limited and much work remains to be done in this area. First, while most children are psychologically resilient and do not develop psychopathology following disaster or terrorism [36], we know little about the resiliency of children with disabilities under the same circumstances. Second, the mental health of individuals with disabilities post-disaster/terrorism has been substantially overlooked by both researchers and clinicians [39].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive factors also influence children's reactions to disasters and terrorism and these reactions similarly can vary given developmental levels or cognitive abilities [35]. Preevent emotional status and prior trauma also affect post-disaster/terrorism reactions and recovery in children [20,36] and several studies report the development of post-traumatic stress disorder (PTSD) in children is strongly related to pre-disaster general mental health [37,38]. For children with pre-existing mental illness, it can be hypothesized that PTSD post-disaster/ terrorism will be more likely, especially when PTSD symptoms are shared with symptoms of the pre-existing mental illness.…”
Section: Disability-related Factors Which May Influence Exposure Cognmentioning
confidence: 99%
“…Previous findings have indicated an association between PTSD and other psychological symptoms such as anxiety and depression (Fan et al, 2011; Goenjian et al, 2011; Lai et al, 2015, 2013), higher risks of behavioural problems, substance abuse and sleep disturbance (Pfefferbaum et al, 2015; Usami et al, 2013). This further highlights the importance of studying more diverse symptoms, particularly psychosomatic symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings also indicate that children whose homes were damaged were more likely to experience anxiety or worries and depressed mood compared to children whose homes were not damaged. Other studies have found disaster experience (both psychological and environmental) to be an important factor in determining a child´s post-disaster mental health (Pfefferbaum et al, 2015; Silverman, 2002; Vernberg, Silverman, La Greca, & Prinstein, 1996). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation